1996
DOI: 10.1126/science.274.5295.2057
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity in Normal Tissue Adjacent to Breast Carcinomas

Abstract: Loss of heterozygosity (LOH) was detected in morphologically normal lobules adjacent to breast cancers. The most frequent aberration was at chromosome 3p22-25; of ten cases with this LOH in the carcinoma, six displayed the same LOH in adjacent normal lobules. This suggests that in a subset of sporadic breast cancers, a tumor suppresser gene at 3p22-25 may be important in initiation or early progression of tumorigenesis. Among sixteen breast cancers with LOH at 17p13.1 and five breast cancers with LOH at 11p15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
326
2
14

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(362 citation statements)
references
References 17 publications
20
326
2
14
Order By: Relevance
“…This study and (James et al, 1997) have confirmed that genetic changes found in DCIS lesions are similar to those found in invasive breast carcinoma. Furthermore, a recent paper has also described some changes in morphologically normal tissue adjacent to breast carcinomas (Deng et al, 1996). One significant conclusion to be drawn from this work is that, even at the preinvasive stage of DCIS, breast cancer is a heterogeneous disease in which the pathway of changes accompanying progression is far from clear.…”
Section: Discussionmentioning
confidence: 67%
“…This study and (James et al, 1997) have confirmed that genetic changes found in DCIS lesions are similar to those found in invasive breast carcinoma. Furthermore, a recent paper has also described some changes in morphologically normal tissue adjacent to breast carcinomas (Deng et al, 1996). One significant conclusion to be drawn from this work is that, even at the preinvasive stage of DCIS, breast cancer is a heterogeneous disease in which the pathway of changes accompanying progression is far from clear.…”
Section: Discussionmentioning
confidence: 67%
“…In surgically resected samples, extensive areas of normal epithelium were frequently present, and the relatively large microdissected foci may have contained more than one clonal or subclonal populations. Allelic losses have also been described in histologically normal epithelium adjacent to or near breast and gallbladder carcinomas (Deng et al, 1996;Wistuba et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Losses at other 3p regions (3p12, 3p14.2, 3p14 ± 21) and the TP53 gene were present mainly in histologically advanced lesions (dysplasia and CIS). Of interest, 3p deletions have been described as early events during the multistage pathogenesis of several other epithelial cancers including head and neck, cervix and breast (Deng et al, 1996;Wistuba et al, 1997b). In contrast, deletions at chromosome 5q and 13q (near the APC and at RB genes) were mainly associated with invasive carcinomas, and were relatively rare in precursor lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent evidence from the late Helene Smith and others have demonstrated that contiguous portions of the ductal systems in the human breast are clonally derived (Tsai et al, 1996). Further studies by this group and others have demonstrated that human mammary tumors in situ share with the surrounding normal parenchyma, common genetic mutations, suggesting that progressive malignant changes toward malignancy in the human breast, as in the mouse, occur as the result of acquired mutation in a multipotent cellular antecedent (Deng et al, 1996;Rosenberg et al, 1997). At the present time the question of whether the genetics of mouse mammary tumorigenesis is directly relevant to human breast cancer remains largely unanswered.…”
Section: The Mouse As a Model For Human Breast Cancermentioning
confidence: 99%